UNKNOWN ISSUES OF DIGITALIZING THE TAX DOMAIN - Dimitrijević, Marina (Serbian political thought, 2024)
The application of digital technologies in the tax domain represents a confirmation of modernization and the turning point in the development of the state’s tax function. Digitalization establishes a new paradigm of managing the tax system and significantly changes the tax‒political reality. The potential of digital technologies is expressively transformative for proceedings of tax relation subjects and offers numerous possibilities for advancing the implementation of taxes and protection of the state’s fiscal interest. The alterations brought about by digital technologies affect tax relations and the perception of the taxation phenomenon in the tax public opinion. The resulting digital innovations of the organization and business model of tax administration generate prerequisites for basic modification of tax procedures and taxpayers’ behaviour in relation to tax compliance. Since the process of digitalizing the tax domain is complex and it seeks to raise taxation to a significantly higher level of development, it is necessary to timely discern, understand, and accept the advantages of this process, but also the accompanying difficulties and challenges, in order to adequately treat them. Digitalization of the taxation domain facilitates the work of tax authorities and compliance with tax regulations, strengthens the state’s digital tax power, empowers the function of tax control of taxpayers, digitally and technologically shapes the tax reality, and gradually paves the “path” for a wider and deeper presence of tax authority in the taxpayer’s life and business. By glorifying the positive points of digitalizing the tax domain and by expecting taxpayers to accept the projected digital‒technological novelties in the tax sphere and to model the existing ways of fulfilling tax obligations, the need for a more comprehensive examination of the reverse side of tax digital novelties, the perception of unknown issues and a more subtle analysis of the uncertainty of their impact on our contemporary tax society and accepted democratic principles and social values, have generally been marginalized. More daring digressions from the discourse of the inevitability of digitalizing taxation which has become almost monopolistically established in numerous countries of the world are less represented, despite the well‒known fact that with the increase of digital capacity, the tax domain becomes more exposed to risks. Superficial and uncritical adherence to digital‒technological trends initiates a series of serious socio-ethical dilemmas in the tax area, which will most certainly be resolved only in the coming years. In the meantime, in circumstances in which the realization of extensive and substantive legal regulation of the use of digital achievements is incomparably slower than the dynamics of their creation for application in administering taxes, the position of taxpayers in the tax procedure will change significantly. The crucial question is whether taxpayers will accept this state of affairs with complete confidence in tax authorities or with an explicit prior request for a more detailed explanation of the effect of digital‒technological changes, as a condition for accepting the remodelling of traditional tax relations and avoiding potential misunderstandings, uncertainties and problems.